Relationship Between History of Exclusive Breastfeeding and the Incidence of Stunting in Toddlers - Jafar, Cindy Puspita Sari Haji (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Stunting is a condition in which the height or length of a toddler is lower than it should be based on age, which is caused by long-term malnutrition, especially in the first 1000 days of life (HPK). The purpose of this study was to determine the relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers. The researcher used the Purposive Sampling Technique. The samples in this study were mothers and toddlers aged 2-5 years who had been registered at the Tilango Health Center, Gorontalo Regency, totaling 92 samples. The results of the study using the Chi-square test obtained ap value of 0.038 (p <0.05), which showed that the variable history of exclusive breastfeeding had a significant relationship with the incidence of stunting in toddlers aged 2-5 years at the Tilango Health Center, Gorontalo Regency. The Health Center is expected to be able to carry out routine monitoring of children at risk of stunting, with special attention to exclusive breastfeeding.